Reducing Spatial Inequality in Indonesia: Off-The-Job Training as A Special Treatment for Underdeveloped Regions - Emil Muhamad (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
Education is one of Human Development Index (HDI) components which plays a vital role. Both theoretically and evidently speaking, the level of education has a positive correlation with income level. However, Indonesia as an archipelago country still can’t be able to provide equitable education for the whole country. Spatial Inequality is thought as the result of this problem. Since outer Java regions are less developed compared to Java, the quality of education is lower as well. The ability of education as income leverage factor is different between regions. Through this study, I compared the rate of return to schooling of both regions and analyze the causes. Furthermore, I examined the differences in the effects of formal education and job training on people in both regions. The aim is to decide what kind of human resources treatment is more effective for each region. This research’s data is collected from the National Labor Force Survey (SAKERNAS) 2014. I used modified Mincer earnings function to analyze the differences between regions. Cross-sectional regression analysis was done by using Ordinary Least Square (OLS) method. I split the data based on groups of the region to compare both rates of return to schooling. The results showed that there are differences in the rate of return to schooling between the two regions for each education level. The effect of training on income level also differs for both regions. Education gives a promising return to income in Java while job training doing it well in outer regions.